Proposalls for an Act for prevention of the great trouble and charge which the honest people of this nation, have been put to; by wrongfull arrests and imprisonments, and for preserving them from such arrests (being upon feygned great actions) at the sute of divers to whom they have owed nothing. And also for an other Act for the taking away the great trouble and charge, which the people of this nation have been put to; by sheriffs, bayliffs, serjeants, &c. to procure arrests and appearances of their debtors, &c. in order to the more speedy satisfying of creditors; for the saving to the people of this nation, between 4 and 500000. pounds yearly, part of the 1500000. pounds, formerly proposed to be so saved yearly, mentioned in the proposalls for creditors and prisoners. With a short explanation in particular, how those 300000. pounds, and more, by these proposalls for creditors and prisoners, will be saved. Offered to the same consideration, as those for creditors and prisoners are. / By Will. Leach of the Middle Temple Gent. [electronic resource] :
Summary goes here